Upper limb revascularization with reversed vein graft and microvascular anastomoses, after brachial artery aneurysm resection, in a child with tuberous sclerosis. - Paz Portinho, Ciro; Alex Longhi, Joel; Muradás Girardi, Adriana; Prestes Valente, Amanda; Jungblut, Carlos Francisco; Belle Manfroi Galinatti, Clara; Ventura Gomes Júnior, Sérgio; Humberto Pereira, Adamastor; Martins Collares, Marcus Vinicius (Clinical and Biomedical Research, 2015)
The authors present an unusual case of a 3-year-old girl who was diagnosed with a fast-growing brachial aneurysm due to tuberous sclerosis. The patient was submitted to aneurysm resection and microsurgical reconstruction with reversed greater saphenous vein graft at the same time. She had a favorable follow-up, without neuromuscular deficits. Doppler ultrasonography has been performed for diagnosis, vein graft choosing, and postoperative follow-up. It is the opinion of the authors that such combined approach may be the routine for pediatric vascular reconstructions. Finally, this reconstruction has been rarely reported in tuberous sclerosis patients.